2019
DOI: 10.3171/2018.4.jns18366
|View full text |Cite
|
Sign up to set email alerts
|

Three types of dural suturing for closure of CSF leak after endoscopic transsphenoidal surgery

Abstract: OBJECTIVETranssphenoidal surgery (TSS) is commonly used for anterior skull base surgery, especially in the sella turcica (sellar) region. However, because of its anatomical position, CSF leakage is a major complication of this approach. The authors introduced a new grading reconstruction strategy for anterior skull base surgery with continuous dural suturing in 2013. In this paper the authors report on their methods and results.METHODSAll patients with sellar or anterior skull base lesions that were removed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Some authors preferred continuous suturing (particularly for high flow ioCSFL and large dural defects) due to even tension distribution, the potential for a tighter seal across the defect, and the requirement of only two knots [ 42 , 67 ]. To offset some of the challenges of this technique (Table 2 ) [ 42 , 64 , 65 , 67 69 ], surgeons describe suturing grafts (fat, fascia, gelatin sponge) directly to the dura in a patchwork configuration for larger defects [ 38 , 58 , 64 70 , 143 ]. By using specialised suture-tying instruments with a sliding-lock-knot technique, suturing was increasingly feasible [ 58 , 65 , 66 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors preferred continuous suturing (particularly for high flow ioCSFL and large dural defects) due to even tension distribution, the potential for a tighter seal across the defect, and the requirement of only two knots [ 42 , 67 ]. To offset some of the challenges of this technique (Table 2 ) [ 42 , 64 , 65 , 67 69 ], surgeons describe suturing grafts (fat, fascia, gelatin sponge) directly to the dura in a patchwork configuration for larger defects [ 38 , 58 , 64 70 , 143 ]. By using specialised suture-tying instruments with a sliding-lock-knot technique, suturing was increasingly feasible [ 58 , 65 , 66 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, different reconstruction concepts and techniques for high-flow CSF leakage through large skull base defects are required. A grading system was proposed and updated to identify an optimally designed reconstruction strategy, and various reconstruction techniques have been introduced [ 13 , 18 , 32 , 42 , 63 ]. A review on endoscopic skull base reconstruction for large dural defects showed a CSF leakage rate as high as 11.5% [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…19,[24][25][26] In addition, dura suturing has been practiced and proven effective. 25,[27][28][29][30][31][32][33][34][35] It was possible that the dura of the anterior skull base was not fully invaded. Otherwise, abdominal fat could be used as the primary reconstruction material.…”
Section: Discussionmentioning
confidence: 99%